Students’ Difficulties In Using Critical Thinking Skill While Reading Narrative Text - Siti Sofiyatul Janah; Nurhaedah Gailea; Udi Samanhudi (Riviera Publishing, 2024)
In the era of globalization and information technology, the ability to think critically is a very important skill for students to have. This ability is not only useful in an academic context, but also in everyday life to make informed and rational decisions. However, research shows that many students still have difficulty in using critical thinking skills, especially when reading narrative texts. This study aims to identify the difficulties experienced by students in using critical thinking skills when reading narrative texts. In addition, this study also aims to find effective teaching strategies to improve students' critical thinking skills in this context. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and document analysis. The research participants were junior high school students who were selected by purposive sampling. The data obtained were analyzed using thematic analysis techniques to identify the main themes that emerged from the data. The results showed that students experienced several difficulties in using critical thinking skills when reading narrative texts, including difficulties in analyzing characters, understanding the storyline, and identifying key themes. In addition, the study found that the use of teaching strategies involving group discussions and open-ended questions can help improve students' critical thinking skills. The implications of this study show that teachers need to develop more interactive and collaborative teaching strategies to improve students' critical thinking skills.